Pendidikan Indonesia Masa Kolonial Belanda dan Pemerintahan Pendudukan Jepang - nurbaity nurbaity (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2018)
Education is an important factor needed by every independent country in the effort of the people's intelligence to build the nation and the country. Education is also a parameter of the progress of a nation characterized by the improvement of the quality of society in living various fields of life. In the course of its history before Indonesia achieved independence, Indonesia experienced two periods in the implementation of education, namely: Dutch colonial education and the Japanese occupation government. Dutch colonial education is not intended to improve the level or culture of the Indonesian people. The contents of the education provided in the form of knowledge and technical skills that can be used to take care of and execute the interests of the Netherlands. Education that does not pay attention to the interests of the Indonesian nation received a response from educational figures of Indonesia, which in the end they organize education tailored to the needs and character of the Indonesian nation. Education held among others Taman Siswa, Education INS Kayu Tanam, Muhammadiyah School, and others. The organization of education undertaken by the Japanese occupation government was part of the Japanese propaganda to win the Greater East Asia War. The education that was run at that time was loaded with military doctrine and discipline. The Japanese government prohibits the use of Dutch language and books, perfecting the Indonesian language and incorporating Japanese language, culture and geography in the learning curriculum for the Indonesian nation.